2005
DOI: 10.1002/lt.20623
|View full text |Cite
|
Sign up to set email alerts
|

A case of successful enteroscopic balloon dilation for late anastomotic stricture of choledochojejunostomy after living donor liver transplantation

Abstract: Biliary complications remain a major concern after living donor liver transplantation. We describe a pediatric case who underwent a successful endoscopic balloon dilatation of biliary-enteric stricture following living donor liver transplantation using a newly developed method of enteroscopy. The 7-year-old boy with late biliary stricture of choledochojejunostomy was admitted 6 years after transplantation. Since percutaneous transhepatic cholangiography was technically difficult in this case, endoscopic retrog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
95
0
3

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 132 publications
(100 citation statements)
references
References 8 publications
2
95
0
3
Order By: Relevance
“…Deep enteroscopy techniques (double-balloon enteroscopy, single-balloon enteroscopy, and spiral overtube-assisted enteroscopy), however, enable access to the anastomosis and subsequent endoscopic management of biliary strictures in LDLT patients with RYHJ, thus obviating the need for more invasive interventions [78,[101][102][103][104]. Sanada et al evaluated the efficacy of double-balloon enteroscopy in 25 pediatric LDLT patients with bilioenteric anastomotic stricture [102].…”
Section: Endoscopic Management Of Biliary Strictures After Ryhjmentioning
confidence: 99%
“…Deep enteroscopy techniques (double-balloon enteroscopy, single-balloon enteroscopy, and spiral overtube-assisted enteroscopy), however, enable access to the anastomosis and subsequent endoscopic management of biliary strictures in LDLT patients with RYHJ, thus obviating the need for more invasive interventions [78,[101][102][103][104]. Sanada et al evaluated the efficacy of double-balloon enteroscopy in 25 pediatric LDLT patients with bilioenteric anastomotic stricture [102].…”
Section: Endoscopic Management Of Biliary Strictures After Ryhjmentioning
confidence: 99%
“…The 2.8−mm working chan− nel allows for the introduction of conven− tional accessories, provided they have 230 cm length available. Choledochojeju− nostomy balloon dilation using DBE was first reported after living donor liver transplantation [4]. In one multicenter study, two patients successfully under− went DBE ERCP and biliary balloon dila− tion after Roux−en−Y reconstruction [5].…”
mentioning
confidence: 99%
“…The median duration of plastic stent patency is around 3 mo (range 2-4 mo), as they are prone to debris deposition in their lumen resulting in obstruction, and risk of cholangitis. This approach has a success rate of 75% to 91% according to different deep ERC can be performed even in patients with Roux-en-Y hepaticojejunostomy [49,50] . A large, multicentric study by Shah et al [51] showed that in patients with surgically altered biliary anatomy, SBE, DBE or rotational over-tube enteroscopy can be used to perform ERC successfully in 88% of patients in whom papilla is reachable.…”
Section: Biliary Stricturesmentioning
confidence: 99%